2022
DOI: 10.1001/jamaophthalmol.2022.0396
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Home Visual Acuity Tests for Telehealth in the COVID-19 Era

Abstract: uring the initial portion of the COVID-19 pandemic, eye care professionals needed to reduce the risk of exposure to patients while continuing to provide highquality health care. The Casey Eye Institute at Oregon Health and Science University saw a decrease in clinic visits to 25% of prepandemic levels in April 2020 and did not return to baseline until March 2021. 1 With the need to limit clinic visits and an increase in the Centers for Medicare & Medicaid reimbursement for telehealth services, 2 teleophthalmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…The role of reliable smart TV based VA self-testing becomes even more important in pandemics that result in major reductions in ophthalmological services with many beneficiaries omitting necessary care, because of fear of infection, inability to access, or cancelation of health services [ 28 , 29 , 30 ]. It is a common belief that in pandemics such as the COVID-19 one, large populations were subjected to unnecessary or inappropriate care, with potentially significant harm to their visual capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of reliable smart TV based VA self-testing becomes even more important in pandemics that result in major reductions in ophthalmological services with many beneficiaries omitting necessary care, because of fear of infection, inability to access, or cancelation of health services [ 28 , 29 , 30 ]. It is a common belief that in pandemics such as the COVID-19 one, large populations were subjected to unnecessary or inappropriate care, with potentially significant harm to their visual capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found LOAs ranging from ± 0.08 to ± 0.49 logMAR 6, 16-23 . Studies varied in the number of aspects changed between reference and index sessions, for example separating tests in time 4,16,20,22,23 , conducting tests in different settings 4,16,18,20,22,23 , using different testers 4,16,18,20,21 , and/or comparing supervised testing with unsupervised self testing 18,20,21,23 , as well as assessing different tests. Each changed aspect widens the LOAs: the current study changed test and setting, undertook tests several days apart and often used a different tester.…”
Section: Discussionmentioning
confidence: 99%
“…The exponential growth witnessed during these past 2 years was mainly fostered by allowing the use of communication solutions like WhatsApp, Facetime, or Doxymity [ 41 , 87 , 88 ], the possibility of seeing both new and established patients regardless of their location, and the relaxing of regulations for licensing and reimbursement due to changes in reimbursement policies by Medicare and private insurers due to the public health emergency [ 18 ]. However, as we see the water surge of the tsunami recede, so will the rate of utilization as the restrictions come back into place and the reimbursement policies change.…”
Section: Lessons Learnedmentioning
confidence: 99%